Paternal Adjustment and Paternal Attitudes Questionnaire: Antenatal and postnatal portuguese versions - Pinto, Tiago Pinto (2017)
The Paternal Adjustment and Paternal Attitudes Questionnaire (PAPA) was designed to assess paternal adjustment and paternal attitudes during the transition to parenthood. This study aimed to examine the psychometric characteristics of the Portuguese versions of the PAPA-Antenatal (PAPA-AN) and -Postnatal (PAPA-PN) versions. A nonclinical sample of 128 fathers was recruited in the obstetrics outpatient unit, and they completed both versions of the PAPA and selfreport measures of depressive and anxiety symptoms during pregnancy and the postpartum period, respectively. Good internal consistency for both PAPA-AN and PAPA-PN was found. A three-factor model was found for both versions of the instrument. Longitudinal confirmatory factor analysis revealed a good model fit. The PAPA-AN and PAPA-PN subscales revealed good internal consistency. Significant associations were found between PAPA (PAPA-AN and PAPA-PN) and depressive and anxiety symptoms, suggesting good criterion validity. Both versions also showed good clinical validity, with optimal cutoffs found. The present study suggested that the Portuguese versions of the PAPA are reliable multidimensional self-report measures of paternal adjustment and paternal attitudes that could be used to identify fathers with adjustment problems and negative attitudes during the transition to parenthood.